2021
DOI: 10.18860/eh.v23i1.11672
|View full text |Cite
|
Sign up to set email alerts
|

Sunan Kalijaga’s Da'wah Strategy in Suluk Linglung and Its Implication to Indonesian Radicalism Movement

Abstract: Sunan Kalijaga was known as a creative da’i in spreading da'wah. One of the media for his da’wah is a literary work entitled Suluk Linglung. In the Suluk Linglung manuscript, two da’wah strategies had been employed by Sunan Kalijaga, both of which were expected to be relevant if applied in Indonesia today, considering the many issues of radicalism. This research is a literature review. Data were collected by using documentation method through a research on Suluk Linglung. Therefore, to dissect the contents of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…It is a plan of action to achieve excellence in a competition or activity. It describes how an effective action plan will be implemented (Yam, 2020); (Muslih et al, 2021); (Bender et al, 2022). Furthermore, it can help someone to determine long-term plans in dealing with the future.…”
Section: The Strategy Of Preachingmentioning
confidence: 99%
“…It is a plan of action to achieve excellence in a competition or activity. It describes how an effective action plan will be implemented (Yam, 2020); (Muslih et al, 2021); (Bender et al, 2022). Furthermore, it can help someone to determine long-term plans in dealing with the future.…”
Section: The Strategy Of Preachingmentioning
confidence: 99%
“…In the modern world, the sociocultural approach to religion is also known as the development model from within. They absorbed the elements of local culture and traditions but still adhered to Islamic principles (Salik, 2019;Muslih et al, 2021). Changes occured within society because of their awareness without any coercion or intimidation.…”
Section: Moderate Islammentioning
confidence: 99%
“…Mutual respect will foster mutual learning that cultural assimilation occurs in multicultural dawah. People can accept Islamic values without being forced (Muslih et al, 2021;Ihsani, et al, 2021)…”
Section: The Interpretation Implications On Moderate Attitudementioning
confidence: 99%
See 1 more Smart Citation
“…He has also used a synchronisation strategy in constructing mosques in Demak (Sabiq 2021). In addition, SKM also spread Islamic teachings through the tembang dolanan 'game songs' (Sonia, Isnawati & Nadhiroh et al 2020) and suluk macapat [religious poetry] (Muslih et al 2021). In fact, in other written sources, it is found that SKM wrote 43 mantras in which Islamic values have been instilled.…”
Section: Introductionmentioning
confidence: 99%